Effects of Rikkunshi-To, a Japanese kampo medicine, on donepezil-induced gastrointestinal side effects in mice - Kouichi Yamamoto; Yuhki Sato; Keisuke Hagihara; Kyosuke Kirikihira; Akito Jotaki; Ayana Michihara; Yumi Miyake (Elsevier, 2022)
Donepezil, an acetylcholinesterase inhibitor, is associated with gastrointestinal symptoms, such as nausea, vomiting, and anorexia, which may affect adherence to continuous therapy. Since Rikkunshi-To, a Japanese herbal medicine, activates the ghrelin signaling pathway and promotes gastrointestinal function, it is administered to prevent gastrointestinal symptoms. We herein investigated whether donepezil-induced gastrointestinal side effects in mice are ameliorated by Rikkunshi-To and if its therapeutic efficacy is mediated by ghrelin. Since pica behavior, the ingestion of kaolin, correlates with nausea and vomiting in humans, donepezil was intraperitoneally administered with or without Rikkunshi-To daily to mice, and food and kaolin intakes were monitored. The effects of donepezil on intestinal motility and a ghrelin receptor antagonist on donepezil-induced pica behavior, anorexia, and changes in intestinal motility were examined in mice treated with Rikkunshi-To. Pica behavior and anorexia were significantly induced by donepezil and significantly inhibited by Rikkunshi-To. Intestinal motility was significantly suppressed by donepezil and promoted by Rikkunshi-To. Furthermore, the therapeutic effects of Rikkunshi-To were antagonized by the ghrelin receptor antagonist. The present results support the therapeutic efficacy of Rikkunshi-To against donepezil-induced gastrointestinal side effects.